History of the Development of Bank NTB Syariah - Wijaya, Muhammad Rifky (PT FORMOSA CENDEKIA GLOBAL, 2024)
This article's goal is to shed light on how Bank NTB Syariah came to be. This piece employs a literature review research strategy with a qualitative focus. The research findings demonstrate that Bank NTB Syariah has experienced numerous changes in response to developments in West Nusa Tenggara (NTB). As a result of the conversion, Bank NTB Syariah is now better able to make its own policy decisions and may see a decrease in the rampant fraud that plagues traditional financial institutions.